ANALISIS SIKAP KREATIF SISWA DALAM PEMBELAJARAN IPA SLTP DI RIAU - Agung Tafirehan; Zulirfan Zulirfan; Yennita Yennita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Creative attitude is an important part of creativity by supporting the creative thingking ability. This study aims to analyze the level of students creative attitude in learning science in junior high school. This research conducted on 218 samples of junior high school students in Riau. The questionnaire about students creative attitude which consists of 3 aspects of creative attitude (making, inquiry/experiment and task commitment) and 15 statement items. The result showed that the creative attitude of junior high school students in Riau was in the good category.Keywords: Creative Attitude, Science